Inheritance Pattern of Qualitative Character Traits in F2 Population of the Bara x Ungara and Dewata x Unggara Crosses - Muhammad Fuad Anshori; Ifayanti Ridwan Saleh; Hari Iswoyo; Muh Farid; Abd Haris Bahrun; Nuniek Widiayani; Dwi Lestari; Nirwansyah Amir (Agrotech Journal, 2022)
The purpose of this study was to estimate the inheritance pattern of qualitative character traits from the F2 population of the Bara x Ungara and Dewata cross. The study was conducted in the experimental garden of Unhas, Tamalanrea sub-district, Makassar, South Sulawesi. The quantitative character traits observed consisted of four characters, namely, the color of the flower corolla, the coloring of the immature fruit, the branching habit, and the nodal color. The results showed that the population of F2 crosses showed a purplish-green color (34) as the dominant color in immature fruits. Crosses with the Ungara variety exhibited a significant contribution to the color in the immature fruit. The nodal color characters is closely related to the duplication interaction pattern between alleles at different loci